The Effectiveness of Reading to Learn (R2L) Pedagogy in Teaching News Text Writing at MTsN 3 Jambi City - Rangga Saputra; Priyanto Priyanto; Arum Gati Ningsih (Jurnal Ilmiah Multidisiplin, 2026)
The Reading to Learn (R2L) pedagogy, consisting of preparatory reading, in-depth reading, collaborative construction, and independent construction, was developed in Australia with the aim of helping students understand academic texts and find useful information within them. This study was designed using a quasi-experimental method with a control group design aimed at testing the extent to which the Reading to Learn (R2L) pedagogy is able to improve students' ability to write well-structured news texts. This study involved 74 seventh-grade students from MTsN 3 Kota Jambi. The research participants were divided into two groups, namely the experimental class (grades VII-9) which consisted of 37 students and the control class (grade VII-4) which also consisted of 37 students. Students in the experimental class were given learning based on the Reading to Learn (R2L) pedagogy, while students in the control class used conventional learning methods. The results of the analysis showed a significance value of 0.000 (Sig. <0.05), which indicates that the Reading to Learn (R2L) pedagogy provides improvements to students' news text writing skills compared to conventional methods. The Reading to Learn (R2L) pedagogy has high flexibility and adaptability to be applied across cultures and languages as a strategic approach, because it is able to bridge the literacy gap while strengthening students' academic text construction skills in various international educational contexts.